Clonidine effects on all-night human sleep : Opposite action of low- and medium-dose clonidine on human NREM-REM sleep proportion - MIYAZAKI, SHINICHI; UCHIDA, SUNAO; MUKAI, JUNKO; NISHIHARA, KYOKO (Psychiatry and clinical neurosciences, 2004)
Norepinephrine (NE) is considered to play a permissive role in the occurrence of rapid eye movement (REM) sleep. Clonidine is an NE α‐2‐receptor agonist, which has been considered to act mainly on the autoreceptors of presynaptic noradrenergic neurons to reduce their release of NE. However, previous studies of clonidine effects on REM sleep have produced controversial results and the effects of clonidine remain uncertain. To clarify the pharmacological effects of clonidine on human sleep, the sleep electroencephalograms (EEG) recorded from 15 young normal subjects after a single administration of either a low (25 µg) or medium (150 µg) dose of clonidine were examined, and fast Fourier transformation (FFT) spectral analyses of the C3‐A2 EEG were performed. Low‐dose clonidine significantly increased the amount of REM sleep and decreased the amount of non‐REM (NREM) sleep during the second one‐third of the drug nights compared to the corresponding hours of baseline night recordings. In contrast, medium‐dose clonidine significantly decreased REM and increased NREM on drug nights compared to baseline nights in the entire night. The opposite actions of low and medium doses of clonidine on NREM‐REM proportion may indicate that low‐dose clonidine mainly affects the α‐2‐receptors on locus coeruleus‐NE neurons presynaptically, reducing the release of NE, whereas medium‐dose clonidine acts more post‐synaptically.